THE RELATIONSHIP BETWEEN READING MOTIVATION AND READING COMPREHENSION AT VOCATIONAL HIGH SCHOOL - Tyas, Kinesti Arining (Journal of English Teaching and Learning, 2024)
This study aimed to find out the relationship between reading motivation and reading comprehension in a foreign language. This research was carried out at vocational high school, with are 99 students of the tenth grade in vocational high school that were randomly selected from five majors: automation and officer governance (OTKP), accounting  a nd financial institutions, online business and marketing, culinary, and computer and network engineering. Data were collected through distributing questionnaire and reading comprehension test. Foreign Language Motivation Reading Questionnaire (FLMRQ) was employed to find out students‟ reading motivation in English and reading comprehension test to find out scores‟ students. The findings, there is no correlation because they have motivation to read in English but their motivation does not run well. Their motivation is not implemented because students‟ ability to read in English is lack or in other words they do not master many English vocabularies. It is seen from the average value of their reading comprehension test is low (56.00) but result of reading motivation is high (72.45).